PERSEPSI MASYARAKAT TERHADAP PEMASANGAN LAMPU TENAGA SURYA DI DESA KEBONDOWO (PROGRAM IDBU): SURVEI KEPUASAN DAN HAMBATAN - R Rizal Isnanto; Heru Prastawa; Endang Purbowati; Ro’fah Setyowati; Meidiana Dwidiyanti; Fifiana Wisnaeni; Bagus Hario Setiadji; Dian Wijayanto; Dita Juni Kurnia (Jurnal Abdi Insani, 2025)
Global warming and the increasing demand for electricity have strengthened the urgency to introduce environmentally friendly technologies at the community level. Kebondowo Village, located in Banyubiru Sub-district, remains limited in nighttime lighting access and relies heavily on conventional electricity, indicating the need for an efficient and sustainable renewable-energy alternative. In response to this condition, Universitas Diponegoro initiated the Iptek Desa Binaan Undip (IDBU) program through the installation of solar-powered street lights across seven hamlets from July to August 2025 as an early effort to support the development of an environmentally friendly village. The objectives of this program were to improve the quality of village lighting, reduce dependence on conventional energy, increase community awareness of renewable energy use, and evaluate the level of public acceptance of the installed technology. The evaluation was conducted using surveys and semi-structured interviews with 40 adult residents, representing diverse professions and age ranges from 28 to 69 years old (mean age 48), to assess user perceptions, perceived benefits, and expectations for program sustainability. The results showed a highly positive response, with 97% of respondents agreeing with the installation of solar lighting and reporting direct benefits, including improved comfort, safety, and energy efficiency during nighttime activities. Furthermore, most residents expressed their expectation for the expansion of solar-powered street lights across all hamlets. These findings confirm that renewable-energy technology has a high level of social acceptance, effectively improves the community’s quality of life, and holds strong potential to be developed as a sustainable program based on rural community empowerment.